The Expressive Impact of Patents - Timothy R. Holbrook (Washington University Law Review, 2006)
Patents represent a quid pro quo between the public and the inventor: in exchange for disclosing the invention, the inventor receives the right to exclude others from practicing her invention. They therefore serve as a source of technical information. Patents also communicate information to markets and companies that serve to reduce various transaction costs, allowing more efficient transactions and investment. Patents consequently communicate various types of information beyond the technical. There is no reason, however, that such messages must be limited to the technical or the pecuniary. This Article explores whether patents, like other governmental acts such as legislation, can create expressive harms. The grant of a patent could communicate a message of inferiority to groups whose identity is tied to their biology. The article analyzes this potential through the paradigm of granting patents on a “gay gene” or other biological process that predisposes a person toward a homosexual orientation. Other conditions implicated by my thesis are the deaf, dwarfs, and high-functioning autistics. These groups do not regard themselves as pathological or in need of “curing,” yet genetic discoveries offer the potential for their elimination through what is effectively privatized eugenics. The grant of a patent on such technologies affords the government’s imprimatur of such controversial technologies. The Article first reviews the scientific status of homosexuality. It then explores whether patents regarding sexual orientation could be a moral signal of inferiority by the government by suggesting that gays and lesbians are pathological. Finally, the Article offers various prescriptions to address this problem.
Keywords: Biotechnology – Patents; Homosexuality; Ethics; Government speech